[18F]FDG PET/CT versus [18F]FDG PET/MRI in the diagnosis of lymph node metastasis in nasopharyngeal carcinoma: a systematic review and meta-analysis - Lei, Junfang; Li, Xu; Xue, Wenbo; Qian, Xinrui; Wang, Tong; Xiang, Yunuo; Zhang, Yangchun; Chen, Meixing; Liu, Zhaohui (Frontiers in Medicine, 2024)
This meta-analysis aimed to evaluate the comparative diagnostic accuracy of [ 18 F]FDG PET/CT versus [ 18 F]FDG PET/MRI in identifying lymph node metastases in individuals with nasopharyngeal carcinoma.Methods: A comprehensive search was executed across PubMed, Embase, and Web of Science through September 2023 to identify studies evaluating the diagnostic precision of [ 18 F]FDG PET/CT and [ 18 F]FDG PET/MRI in detecting lymph node metastasis in nasopharyngeal carcinoma. Sensitivity and specificity were assessed through the DerSimonian-Laird method, incorporating the Freeman-Tukey transformation.The meta-analysis encompassed nine articles, involving a total of 916 patients. The overall sensitivity and specificity of [ 18 F]FDG PET were 0.95(95%CI: 0.88-1.00) and 0.95(95%CI: 0.84-1.00). The overall sensitivity of [ 18 F]FDG PET/CT was 0.94(95%CI: 0.85-0.99), whereas [ 18 F]FDG PET/MRI achieved a sensitivity of 1.00(95%CI: 0.94-1.00). The findings reveal that [ 18 F]FDG PET/CT demonstrates comparable sensitivity to [ 18 F]FDG PET/MRI (P = 0.20). The overall specificity of [ 18 F]FDG PET/CT was 0.94(95%CI: 0.82-1.00), whereas [ 18 F]FDG PET/MRI exhibited a specificity of 0.98(95%CI: 0.93-1.00). Additionally, the results suggest that [ 18 F]FDG PET/CT offers similar specificity to [ 18 F]FDG PET/MRI ( P = 0.11).Conclusions:[ 18 F]FDG PET demonstrates high sensitivity and specificity in identifying lymph node metastasis in nasopharyngeal carcinoma. Furthermore, [ 18 F]FDG PET/CT exhibits comparable sensitivity and specificity to [ 18 F]FDG PET/MRI.